Dexmedetomidine infusion overdose during anesthesia: A case report. Issue 2 (27th January 2020) - Li, Christine; Clifford, Michael
Abstract: A 12‐kg infant was given intravenous dexmedetomidine 0.2 µg kg ‐1  min ‐1 as an adjunct for general anesthesia. The 60‐fold increase in dexmedetomidine infusion rate caused a biphasic response with initial hypertension followed by bradycardia and hypotension requiring inotropic support. No postoperative or long‐term sequelae were noted. Dexmedetomidine infusion is usually delivered as µg kg ‐1  h ‐1 .